Expanding diversity within phenylketonuria in ecuadorian patients: genetic analysis and literature review of newborn screenings - Alex S. Aguirre; Edison Haro; Alberto Campodónico; Benjamín Arias-Almeida; Alissa Mendoza; Juan Pozo-Palacios; Vanessa Isabel Romero Aguilar (BMC, 2024)
Abstract Phenylketonuria (PKU) is an autosomal recessive metabolic disorder caused by a deficiency in the phenylalanine hydroxylase (PAH) enzyme, leading to the accumulation of phenylalanine and its metabolites, which are toxic to the central nervous system. Without treatment, PKU can result in severe intellectual disability and neurological issues. This study aims to present the first cohort of clinically described Ecuadorian PKU patients, analyzing genotype-phenotype correlations and comparing these variants with global databases to improve diagnosis and treatment in Ecuador. Detailed clinical histories were collected, and an analysis of genotype versus phenotype (affected protein domain) of the variant was performed. Among the PAH genotypes identified, we found 15 distinct variants, with c.[754 C > T](p.Arg252Trp); [754 C > T](p.Arg252Trp) being the most frequent genotype (23.68%), followed by c.[1045T > C](p.Ser349Pro); [1045T > C](p.Ser349Pro) (15.79%) and c.[441 + 5G > T]; [754 C > T](p.Arg252Trp) (13.16%). Additionally, several unique genotypes were identified, such as c.[140G > A](p.Ala47Val); [140G > A](p.Ala47Val) and c.[331 C > T](p.Arg111Ter); [1243G > A](p.Asp415Asn), which are not commonly reported in other populations. Most genotypes were heterozygous (63.2%). The majority of variants were missense variants (66.6%) affecting the catalytic domain (53.3%). The highest phenylalanine levels were found in patients with c.[754 C > T](p.Arg252Trp); [754 C > T] (p.Arg252Trp) (2700 umol/L). Phenotypic data were available for 11 patients, showing 45.45% with classic PKU, 45.45% with mild hyperphenylalaninemia, and 9% with mild PKU. There was a 63.6% concordance with the BIOPKU database. Five low-frequency genotypes not reported in BIOPKU were identified, suggesting unique regional variants. Our study highlights the genetic complexity of PKU in Ecuador, with a high prevalence of unique variants not commonly found in other regions. This underscores the necessity for region-specific genetic analysis to improve PKU diagnosis and treatment. The findings emphasize the importance of tailored therapeutic strategies and continued research to enhance outcomes for PKU patients in Latin America.